Cloning and expression of Plasmodium falciparum lactate dehydrogenase (PfLDH) in Escherichia coli BL21(DE3) - Fifi Fitriyah Masduki; Yeni Hotimah; Rosalia Rani; Arsyam Mawardi; Euniche R.P.F. Ramandey; Azzania Fibriani; Sony Suhandono (Indonesian Society for Biochemistry and Molecular Biology, 2019)
Background: Immediate and accurate diagnosis of malaria is essential for effective control of this disease. Immunochromatographic based rapid diagnostic tests (RDTs) are economical, simple to perform, and provide results in a relative short time, can be useful to assist effective management of malaria. The commercially available malaria RDT in Indonesia is still imported. Therefore, an effort to produce malaria RDT independently is necessary. One of the biomarkers used in RDTs is Plasmodium lactate dehydrogenase pLDH. The production and accumulation of pLDH during asexual stage or blood-stage in all human infected malaria parasites can be used to indicate parasites viability, which is correlated with the number of parasites present in the plasma of infected patients. Objective: The aim of this research is to produce recombinant PfLDH in Escherichia coli BL21(DE3). Methods: PfLDH gene was cloned into pET30a expression vector to obtain a 6.2 kbp recombinant plasmid pET30a-PfLDH. E. coli BL21(DE3) was transformed with pET30a-PfLDH using the heat shock method. Then, E. coli BL21(DE3)- pET30a-PfLDH was cultured in LB broth containing 50 mg/mL kanamycin and was induced by 1mM IPTG at 37oC. Results: SDS-PAGE and Western Blot analysis showed that recombinant PfLDH was expressed with molecular mass 30 kDa. Conclusion: Recombinant PfLDH is expressed in E. coli BL21(DE3) and can be used in further research for producing rPfLDH as a biomarker for malaria RDT development.